(untitled) (UNED Research Journal, 2021)
Introduction: The sylvatic cycle of rabies is a significant sanitary burden in Central America. The Costa Rican government monitors cases since 1985 and infections from bats are still reported for wild animals, livestock, and humans, generating a need of further pathogen characterization in the region. Objective: To compare rabies phylogenetic analyses from complete genomes with nucleoprotein gene studies. Methods: For the phylogenetic analyses we used four rabies tissue samples collected in 2018, and generated complete genomes by Next-Generation sequencing (NGS). We also extracted RNA from tissues of confirmed cases and generated ssDNA using several primers. Double-stranded DNA was generated and used to generate genomic libraries. Results: We describe, for the first-time, the complete genome of four sequences of the rabies virus isolated in Costa Rica in 2018. Complete genome trees resembled the topology of nucleoprotein gene trees. All isolates were related to Desmodus rotundus. One sample group into Lineage (L)2, and the remaining samples group in L1, matched previous reports from regional rabies viruses. Conclusion: Our method produces valid viral assemblies from clinical specimens without target enrichment or viral isolation.